THE CORRELATION BETWEEN SELF-CONFIDENCE, MOTIVATION, AND STUDENTS’ SPEAKING ACHIEVEMENT IN SENIOR HIGH SCHOOL - Arofah, Erlin Rizka (Journal of English Teaching and Learning, 2024)
This study aims to investigate the relationship between self-confidence, motivation and speaking achievement. The present study used correlational research approach which examine whether two or more variables have correlation or not. There were 39 respondents that were taken 25 % from five classes in the eleventh graders at one of secondary school in Banyuwangi.  The instruments used were self-confidence and motivation questionnaire and students’ speaking achievement test. Pearson product moment and scatter plot in SPSS were used to analyze the data so that there was a result whether there is correlation or not. The finding revealed that there is no significant correlation between self-confidence and speaking achievement. Not only the self-confidence which is there was no correlation but also motivation and speaking achievement too.